Pengaruh Past Performance, Fund Age, Expense Ratio dan Fund Cash Flow Terhadap Kinerja Reksa Dana (Studi Kasus Reksa Dana Saham Periode Tahun 2013-2019) - Deviana, Shintia; Hifni, Syaiful; Limarjani, Sustinah (Politeknik Negeri Ambon, 2024)
This study was conducted to examine and analyze the effect of (1) To determine and analyze the effect of past performance on the performance of mutual funds; (2) To determine and analyze the effect of fund age on the performance of mutual funds; (3) To determine and analyze the effect of the expense ratio on the performance of mutual funds; (4) To find out and analyze the effect of fund cash flow on the performance of mutual funds. The method used in this research is multiple regression analysis. The data analysis tool used is SPSS, the sample in this study obtained 12 investment managers obtained using purposive sampling method. The results show that past performance, fund age, expense ratio and fund cash flow have a significant effect on the performance of mutual funds listed on the Indonesia Stock Exchange (IDX) for the period 2013-2019. The results of this study prove the effect of past performance, fund age, expense ratio and fund cash flow on the performance of mutual funds through empirical testing using the singnaling theory on sample companies on the Indonesia Stock Exchange. The practical part of this research is to provide information, references, and considerations for companies or investment managers who are members of the Indonesia Stock Exchange which publish financial reports for decision making for the management.